Stereoisomerism in Tetrametallic Propeller‐Like Complexes: A Solid‐State and Solution NMR Study on a Tetragallium(III) Derivative. Issue 1 (25th November 2021) - Cornia, Andrea; Mucci, Adele; Briganti, Matteo; Bridonneau, Nathalie; Nava, Andrea; Nicolini, Alessio
Abstract: Tetragallium(III) complex in [Ga4 (L 4‐Py )2 (dpm)6 ] ⋅ EtOH, with H3 L 4‐Py =2‐(hydroxymethyl)‐2‐(pyridin‐4‐yl)propane‐1, 3‐diol and Hdpm=dipivaloylmethane, was investigated as a diamagnetic analogue of tetrametallic, propeller‐like single‐molecule magnets (SMMs). The chiral molecular structure partitions the six CH2 protons of each tripodal (L 4‐Py ) 3− ligand into two diastereotopic sets. The two signals were clearly detected by 1 H NMR spectroscopy in C6 D6, proving that Λ and Δ enantiomers interconvert slowly over NMR timescale. Density functional theory calculations provided quantitative agreement with the observed values of chemical shifts and scalar coupling constants across both geminal and long‐range interaction pathways. The solid‐state structure suggests the occurrence of a lower symmetry stereoisomer (27 mol%), which was clearly identified in the NMR spectra. Since high spin Fe 3+ forms distinctly more inert complexes than Ga 3+, comparable or greater configurational stability is expected for the isostructural Fe III 4, Fe III 3 Cr III, and Fe III 3 V III SMMs, which are difficult to investigate by solution NMR because of the strong paramagnetism. Abstract : A chiral tetragallium(III) complex isostructural with the family of propeller‐like Fe III 3 M III single‐molecule magnets (M=Fe, Cr, V) was prepared and found to give spectacularly resolved 1 H NMR spectra in solution. We clearly identified two diastereoisomers with different symmetry in solution and used density functional theory calculations to demonstrate that their Λ and Δ optical antipodes interconvert slowly over NMR timescale.